2007
DOI: 10.1007/s10658-007-9130-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection

Abstract: Papaya ringspot virus (PRSV) HA 5-1, a nitrous acid-induced mild mutant of severe strain HA, widely applied for control of PRSV by cross-protection, was used to study the genetic basis of attenuation. Using infectious clones, a series of recombinants was generated between HA 5-1 and HA and their infectivity was analyzed on the systemic host papaya and the local lesion host Chenopodium quinoa. The recombinants that contained mutations in PI and HC-Pro genes caused attenuated infection on papaya without conspicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Based on sequence analysis, it has been hypothesized that the P1 protein has a role in adaptation to the host of potyviruses (Adams et al ., 2005; Valli et al ., 2007). In support of this hypothesis, nucleotide changes in the P1 sequence were associated with PPV adaptation and symptom modulation in N. clevelandii (Salvador et al ., 2008a), and with attenuation of Papaya ringspot virus in papaya (Chiang et al ., 2007). Furthermore, substitution of the PPV P1 cistron by the corresponding region of the Tobacco vein mottling virus (TVMV) genome did not affect PPV infectivity in common PPV/TVMV hosts, but did prevent infection of peach, which is not a host for TVMV (Salvador et al ., 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence analysis, it has been hypothesized that the P1 protein has a role in adaptation to the host of potyviruses (Adams et al ., 2005; Valli et al ., 2007). In support of this hypothesis, nucleotide changes in the P1 sequence were associated with PPV adaptation and symptom modulation in N. clevelandii (Salvador et al ., 2008a), and with attenuation of Papaya ringspot virus in papaya (Chiang et al ., 2007). Furthermore, substitution of the PPV P1 cistron by the corresponding region of the Tobacco vein mottling virus (TVMV) genome did not affect PPV infectivity in common PPV/TVMV hosts, but did prevent infection of peach, which is not a host for TVMV (Salvador et al ., 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…1c, there are also reports of attenuated potyviruses (Chiang et al 2007;Lin et al 2007b;Yambao et al 2008). When an attenuated strain (HA5-1) of PRSV was compared with its parent strain HA using an infectious cDNA clone, two amino acid substitutions among three in the C-terminal region of P1 at aa positions 309 and 481, and two of four in HC-Pro at aa positions 753 and 944 of HA5-1 appear to be critical in symptom attenuation in papaya (Chiang et al 2007). In a comparison of attenuated and severe strains of Clover yellow vein virus (ClYVV), two amino acid substitutions in HC-Pro were found to be responsible for symptom attenuation (Yambao et al 2008).…”
Section: Potyvirusmentioning
confidence: 99%
“…Once the mild strain has been inoculated it can trigger strain-or sequence-specific resistance against the challenge virus. Many researchers have found that mutations on viral silencing suppressors can attenuate severe symptoms, e.g., mutations in the silencing suppressor HC-Pro from potyvirus (Gal-On 2000; Chiang et al 2007;Lin et al 2007). In addition, mutations on the 126 kDa replicase, another silencing suppressor from the pepper mild mottle virus (PMMoV) resulted in attenuated symptoms and provided cross-protection on pepper plants (Yoon et al 2006).…”
Section: Cross-protectionmentioning
confidence: 99%